Design and implementation of the motion control system of the mobile robot based on PID - Xiao-ping DU; Kai-qi ZHAO (Tongxin xuebao)
A kind of motion control system of the autonomous mobile robot was introduced,and a PID closed-loop control method was proposed that controlling the robot moving along the expected direction and speed effectively through establishing the kinematics model of the autonomous mobile robot.In addition,the modular software program and the hardware system were developed whose main components were the STC12C5A60S2 microprocessor,the MC33886 motor driver chip and hall sensors.Finally,experiments proves the control method and the system effective and stable.